Competencies Development Based on Thinking-Based Learning in Software Engineering: An Action-Research - Flores, Andrés Paul Moya; Alencar, Fernanda Maria Ribeiro de (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2020)
For a long time, the teaching of Software Engineering (SE) has been carried out in a traditional way without taking into account relevant aspects of the student's personality reflected in their learning. There is still a lack of research focused on SE that promotes adequate teaching methods so that new generations of students and future professionals have a humanistic, critical and reflexive formation. A novel teaching method called Thinking-based Learning (TBL) was proposed to develop effective thinking in students using thinking skills, habits of the mind and the metacognition during the teaching of subject content. The action research as a methodology to improve their teaching practices in education has been seen as a positive change in educational practices. The aim of this research was to perform an action research based on TBL method to assist in the development of competencies that are less attended by traditional methods currently used during the teaching and learning process of students in SE. Moreover, a Systematic Literature Review (SLR) was conducted to identify gaps in the contribution of teaching methods in SE until the present. The data are obtained by comparing the competencies achieved with TBL with the traditional methods previously used in the discipline, and additionally with the data obtained from the SLR. The results indicated that critical thinking, autonomy, problem solving and creativity were the most developed competencies by students during the course period. We are planning to expand the TBL and applying it in other disciplines of the same course as well as in other research areas to determine its functionality and interdisciplinarity. We hope that this experience with TBL will encourage the development of competencies among SE teachers.